2018
DOI: 10.4172/2375-446x.1000144
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities of Small Scale Poultry Production System in Jigjiga Zone, Somali Regional State, Ethiopia

Abstract: Background: Small scale Poultry production are used by farmers in order to generate cash income and as a source of food for domestic consumption however, the production sector is constrained by disease, predators, poor housing, poor management, lack of feed, low market prices and lack of markets. This study aimed to identify challenge and opportunities available for small scale poultry production in Jigjiga zone of Somali regional state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 2 publications
4
6
0
1
Order By: Relevance
“…Majority of the households used Scavenging with supplement feeding mechanism for their chicken. This report agree with report of Mohamed et al (2016) who report more than 80% of the households supplement their chicken with one hand full of grain twice per day. This might be due to highest number of households practiced semi-intensive production system, chicken have no chance to forage wide area.…”
Section: Syngamus Trachea Sppsupporting
confidence: 92%
See 3 more Smart Citations
“…Majority of the households used Scavenging with supplement feeding mechanism for their chicken. This report agree with report of Mohamed et al (2016) who report more than 80% of the households supplement their chicken with one hand full of grain twice per day. This might be due to highest number of households practiced semi-intensive production system, chicken have no chance to forage wide area.…”
Section: Syngamus Trachea Sppsupporting
confidence: 92%
“…High number of households managed their chicken in separate chicken houses and cleans regularly. This report in line with the report of Mazengia et al (2012) and Mohamed et al (2016) reported 81.5 and 85.4% of households used to manage their chicken in Separate chicken house respectively. While it contrasts with the report of Salo et al (2016), 76.7% of the households have no separate chicken house.…”
Section: Syngamus Trachea Sppsupporting
confidence: 91%
See 2 more Smart Citations
“…Pemerintah Pakistan juga bertekad memperbaiki kualitas hidup masyarakat dan untuk menangkal kelaparan serta kekurangan gizi dengan membuat sektor pertanian menjadi produktif, efisien dan secara ekonomi menguntungkan (Memon et al, 2015). Produksi unggas skala kecil merupakan bisnis rumah tangga yang berkembang di seluruh negara berkembang sebagai sumber pendapatan (Mohamed et al, 2016: Maoba, 2016.…”
Section: Pendahuluanunclassified